Sanctions and Their Effects on the Labor Market and the Economy - Afsaneh Zareei; Eskil Wadensjö (Institute of Labor Economics (IZA), 2024)
Sanctions have a long history dating several centuries. There has been a significant increase of sanctions after World War II. Those against Iran and Russia are at present in focus for the discussion of sanctions, but also other countries as Cuba and North Korea are sanctioned. There are several different forms of sanctions as for example those on trade, financial and travel and there are also sanctions directed on individuals. The sanctions imposed multilaterally have most effects and have increased significantly. Sanctions have several effects for the countries being sanctioned. There are for example effects of sanctions on economic development, foreign investments, trade flows, employment, wages and emigration (brain drain).
Keywords: F22; F51; F53; J61; 330; international sanctions; emigration; employment; Iran; Russia; North Korea